2022
DOI: 10.3389/fnut.2022.879363
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dairy Intake and Executive Function in Chinese Children Aged 6–12 Years

Abstract: Association between dairy intake and executive function remains controversial, especially among children, a population with fast-developing executive functions. This study aimed to explore this topic. Additionally, we further distinguished the role of dairy intake types (full- or low-fat milk or yogurt) in this relationship. This survey included 5,138 children aged 6–12 years. Dairy intakes were assessed by validated questionnaires. Executive function was measured by the behavior rating inventory of executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Fluid milk was identified as the primary breakfast item across all three breakfast patterns in the study population. They had better executive performance compared to those who skipped the breakfast, which is consistent with several studies ( 14 , 26 , 40 ). An observational study in Chile reported that adolescents who consumed dairy for breakfast showed higher cognitive performance ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Fluid milk was identified as the primary breakfast item across all three breakfast patterns in the study population. They had better executive performance compared to those who skipped the breakfast, which is consistent with several studies ( 14 , 26 , 40 ). An observational study in Chile reported that adolescents who consumed dairy for breakfast showed higher cognitive performance ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
“…An observational study in Chile reported that adolescents who consumed dairy for breakfast showed higher cognitive performance ( 14 ). One study from China found that a high dairy intake was related to better executive function performance compared to low intake among children aged 6–12 ( 26 ). An interventional study of overweight and obese adults indicated that a high dairy diet has the potential to improve working memory ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation